Dermatology on Operation HERRICK. Issue 3 (1st September 2012) - Driver, Jamie; Simpson, R; Wall, C; Nelson, TG
Abstract : Objectives: To identify the dermatological conditions affecting British troops in Afghanistan, understand how they are treated and identify potential areas for improvement. Methods: Data was collected from the Defence Analytical Services and Advice agency and the Operational Emergency Department Attendance Register via the Disease and Non Battle Injury working group. Additional data was collected from J4 – Medical Permanent Joint Headquarters. Treatment information from Clinical Guidelines on Operations (CGOs), Medics' protocols, and primary care module composition was reviewed. Results: Dermatological conditions accounted for 1 in 5 attendances to a Role 1 Medical Treatment Facility during the study period. They were consistently in the top five reasons for working days lost, and had a comparatively high hospital admission rate (0.3/1000 Population at Risk (PAR)/month) and a repatriation rate similar to other medical specialties such as respiratory and neurology (0.1/1000 PAR/month). Treatment appeared to be adequate based on declining return attendance numbers, although CGOs were found to lack dermatological protocols and medic protocols were eight years old and not specific to the current operational requirements. Conclusions: Although treatments are working for dermatological conditions, areas for optimisation of health care have been identified, such as updating medic protocols to include campaign specific information and latest guidelines in the CGOs. Pre-deployment dermatologist-devised treatment plans and tele-consults may also help keep soldiers with pre-existing skin complaints in theatre.